Tjäderns (Tetrao urogallus L.) vinterdiet i norra Sverige : är gran (Picea abies) viktig i vissa habitat? - Öberg, Staffan (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2011)
In Scandinavia, capercaillie are often associated with pine trees (Pinus sylvestris) in winter, with pine needles as the main diet. Few dietary studies have been conducted in Sweden and winter diet is subject to little debate. The interesting thing is that this "pine specialist” is also found in spruce (Picea abies) forest habitats where pine is scarce or unavailable. In many studies outside Sweden (primarily Central Europe) spruce is regularly observed in the winter diet, but I have found no reports on the selection of the diet in spruce forest areas in Sweden. In this study, I examine the diet of capercaillie (Tetrao urogallus L.) in regions with little pine to find out if spruce may have been overlooked as a alternative winter food source. I studied the capercaillie winter diet in four geographically different areas in northern Sweden by using faecal analysis. I wanted to test if there were differences in the winter diet eaten by capercaillie in different habitats, particularly those with hardly any pine. Winter droppings were collected during snowy conditions in April 2010. Each dropping consisted of about five pellets from the same capercaillie. Of these, I weighed randomly up and analyzed 1 gram of feces. Overall I analyzed a sample of 62 different droppings by microhistological faecal analysis. In total, I counted 28 775 fragments of the epidermis and pieces of needles from these droppings. My analysis revealed differences in the diet in areas with different habitats. Pine was eaten to a large extent whenever it was available. In spruce-dominated forests without pine, mainly spruce was eaten. Juniper (Juniperus communis) were a small part of the capercaillie’s diet in all the areas I investigated. Birch (Betula pubescens) were also eaten in small part, especially in areas with much spruce. Overall, my analysis thus suggests that, compared to previous studies in Scandinavia, capercaillie are more flexible in their winter diet than previously thought and that spruce can be an important food for them in some areas.